Hareketli tabanlı açık kanallarda kısmi sürüntü maddesi hareketi üzerine bir inceleme - Kapdaşlı, M.Sedat (Fen Bilimleri Enstitüsü, 1982)
Akarsularda katı madde taşınması, akarsudan alman suyun çeşitli amaçlarla kullanılması sırasında değişik ve çözümlen mesi çok güç problemler ortaya çıkartabilmektedir. Ancak ta şınan katı maddenin miktarı, cinsi, taşınma şekli gibi veri lerin belirlenmesiyle akarsuyun üzerine plânlanan bir su ya pısı doğru ve amaca uygun bir şekilde boyutlandırılabilir. Taşınan katı madde ile ilgili bilgilerin eksikliği veya doğ ru olmaması gibi nedenlerle sanat yapısı olarak doğru plân lanan su yapılarının atıl hale gelmesi mümkündür. Pratikte bu tip yapılara sık sık rastlanmaktadır. Akarsularda katı madde taşımsı olayı çok sayıda parametrenin etkisi altında meydana gelmekte olup bu parametrelere bağlı olarak çok kar maşık bir yapıya sahiptir. Bu nedenle akarsularda katı madde hareketi ile ilgili pek çok araştırma yapılmış olmasına kar şılık, konu tam olarak aydınl atı lamamı ş ve her koşulda uygu lanabilen genel geçerli bağıntılar elde edilememiştir. Bu konuda şimdiye kadar yapılan çalışmalar gözden geçi rilirse akarsu tabanında bulunan karışımın içindeki danele- rin mevcut akım şartlarında bir kısmının hareket edip bir kısmının etmediği "kısmî sürüntü maddesi hareketi" olayının çok az incelendiği ve yeterince aydınlatılmadığı görülür. Kısmî hareket halinde karışımdaki bütün danelerin hareket halinde olduğu genel hareket durumunda geçerli olan eşitlik leri kullanmak mümkün değildir. Bu çalışmada kısmî sürüntü maddesi hareketi genel olarak ele alınarak olay fiziksel ve teorik yönleriyle belirlenmeye çalışılmıştır. Birinci bölümde akarsularda katı madde hareketi ile il-. gi-li çalışmaların genel bir değerlendirilmesi yapılmış ve kısmî sürüntü maddesi hareketini yakından ilgilendiren ça lışmalar ele alınmıştır. II îkinc i bölümde "kısmî s ürün t ü maddesi hareketi"ile il gili teorik düşünceler açıklanmaya çalışılmıştır. Bu düşün celer yardımıyla kısmî harekette taşınan malzeme granülomet- risinin bulunması, dane sınıflarının taşınma yüzdelerinin belirlenmesi gibi kısmî s ürüntü maddesi hareketi değişik yön leri açıklanmaya çalışılmış ve kısmî harekette katı madde debisini bulmak için o G = Y. et. B.a.d (1-n) s s o o ifadesi teklif edilmiştir. 1 - m a-f^Pi]] Üçüncü bölümde teorik düşünceler sonucunda ortaya çıkan çeşitli parametre ve katsayıların olaya etki eden parametre lerle değişimini deneysel yolla bulmak amacıyla kurulan de ney düzeni ile yapılan deneylerin özellikleri açıklanmaya çalışılmıştır. Dördüncü bölümde deneylerden elde edilen verilerin de ğerlendirilmesi yapılmış ve teorik olarak ortaya konan düşün celerin geçerliliği ile ancak deneysel yolla bulunabilen pa rametre ve katsayıların olaya etki eden parametrelerle deği şimleri belirlenmiştir. Parametre ve katsayılar için verilen çeşitli eğrilerin analitik ifadeleri elde edilerek pratik amaçlar için kullanılabilir hale getirilmişlerdir. Beşinci bölümde tez çalışmasından elde edilen sonuçlar toplu halde verilmiştir.

The sediment transportation in water courses may couse a variety of problems in diverting or storing stream water for various purposes, in river navigation as well as in constructing river structures such as diversion dams, storage dams, training works, bridges and the like any water structure can be designed properly therefore provided that the data about the amount, quality and way of transportation of sediment are predicted. The lack cf these data may create problems to the scale of rendering the resultant water structures ineffective or even useless. There are many examples of such structures in engineering practice. The abudance of the interrelated pramaters involved extremely complicates the sediment transportation phenomenon. The governing equations of the complete motion of the bed load are inapplicable in the cases where only some of the particles in the river bed undergo motion whilst the rest stay stationary. Due to lack of sufficient development in this area, this work has been primarily intended to investigate the partial motion of the bed load. The phenomenon has been studied with respect to in theoretically as well as experimentally £.nd weight has been placed to the following aspects. IV a) In complete motion at the bed load, size distribution of the transported material is the same as that of the bed material. When partial motion occures howewer they materially differ from each other. In the case of the partial motion of the transported material comprises of relatively fine material and its size distribution can be determined through the distribution parameters of the transported material which can be defined as follows. 3 The percentage of the sediments with a particular diameter within the transported material The percentage of the same sediments in the river bed material A different value of the distribution parameter will exist for each particular diameter in the bed material This parameter will represent the effects of all factors involved in the motion of bed material. The variation of 6 with respect to various flow conditions has been determined from the laboratory test results. Denoting the wright percentage of the sediment groups in the bed load by 3^ the following relations have been obtained. m4I m«I -m^e Ao~ mi e *Q 320 - (^ + n2 £nl). Q -TLyTlr&TlI 625 = (n5 + n6 JLiiD.Q -ny-ng &nl m "m6I -m7e 330 = m5.e. Q 81 -k2I -k4I g.« kx e - k3 Q 50 "V -k8I B - k5 e -k? Q £80 ~ l\ V*Q ?BB5---y v,Q Percentage, x" of the grains with diameter d in the transported material can be determined by means of these parameters from the percentage x, corresponding to the same grain diameter in the material as follows X2 ~ \ ' Xl b. In the case of partial motion any mixture in the river bed contains stationary and partially mobile grains in addition to completely transported portions. VI The determination of the limiting diameter of these different groups and the calculation of the percentage of the transported portion can be realized with the aid of experimentally derived curves and relations. The particle diameter ds which divides the sediment groups transported perpetually and tempi rarily in the case of partial sediment motion in given by ds = m9 + m10. Q + m11 inl where the parameters vary with the grain size distribution of the river bed material. These parameters were experimentally determined. Due to the statistical character of the phenomenon the exact expression of the limiting diameter for the stationary sediment is difficult and even impossible to state. However, for a specific period of one hour which is taken as the standart test period it can be approximated by do= n9 + n10-Q+nll.q'1 percentage of the partially transported particles in the bed material can be defined as follows : If the quantity of particles with diameter d- is pi in a certain amount of material G in the river bed and it this quantity attains a value of. pj..t in the same amount of material during the partial motion then the percentage of the transported material corresponding to the particles with diameter d^ is given by f. = a. i 4 Cdi - d )2 (ds - dö)2 VII where a is a coefficient and is expressed in terms of d/ds as follows d. a. = 1,30 - 0,30 -^i- h d s The curves depictinş percentage of the transported material are given in figures 4.29-4.47. c. A number of equations exist for the calculation of sediment discharge in rivers. However all these equations apply only to complete motion of the bed load, and no formula has so for appeared in literature for the computation of the amount of transported material in partial motion As a result of theoretical and experimental works such a formula is developed here as Gs = a.B.X0. d^ys (1-n) [ 1 -[^ (1-^),Pi ]] where f is percentage of transported material p denotes the quantity of particles.with diameter d^ and a is a coefficient given by o= e-j.Q + Eo-Q* ^nI ~ zr> There is a transition region between partial and complete motion with continously changing limits for a values around 1. The following general conclusion can be remarked. 1. River bed grain size distribution plays a significant role in the partial sediment transportation and no single variable is sufficient to fully represent this role. VIII 2. Although the fine and coarse materials are carried as a mixture their motions are governed by different rules. In conclusion, it was seen that the partial motion, being more complicated than the complete motion of the bed load, cannot be covered by the equations derived for the later case. This work which constitutes a general framework to the study of partial motion of the bed material is believed to establish a basis for future investigations in this field.
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1982
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 1982
Keywords: Akarsu tortuları; Kanallar (Hidrolik Mühendisliği); Tortu taşınması; River sediments; Channels (Hydraulic engineering); Sediment transport